Procrastination as a factor of students’ learning activities (Actual Problems of Psychology in Educational Institutions, 2022)
The article analyzes the different views of scientists on thephenomenon of procrastination, considers the main reasons for delayingthe solution of problems. The author proves the relevance of studyingprocrastination as a factor in creating an educational environment inhigher education institutions. The aim of the study was chosen theoreticaland empirical analysis of the phenomenon of procrastination in theeducational activities of students. The significance of motivationalinsufficiency, perfectionism and anxiety in the structure of procrastinationis revealed. The results of an empirical study of the influence of learningmotivation on student procrastination are presented. It was stated thatthe tendency of higher education seekers to postpone solving tasks is notcorrelated with the age of the respondents.